Design and Construction of 100 WP Capacity Tracker Solar Panel using VDI 2206 Method - HERMAN BUDI HARJA; MOHAMMAD YAZID DIRATAMA; FITRIA SURYATINI; MUHAMMAD FATURROHMAN; PRADIKA NOVIANDANI (Institut Teknologi Nasional, Bandung, 2025)
There are main issues in optimizing the energy conversion of solar panels, including (1) the movement of the sun's position and (ii) the best capability of solar panels to capture sunlight, which must be perpendicular to the sun's rays. The objective of this research is to conduct a study into the design and development of a solar panel tracking system, specifically to obtain the effectiveness value of the tracking system. The VDI 2206 method is used in the design, which integrates three main systems: mechanical, electronic, and information technology. Based on the test results, the performance of the solar panel tracker increased by 48.38%. With a tracking system power requirement of 5.51%, the percentage increase in the net energy gain of the tracker solar panel is 40.2% compared to static solar panels. Therefore, solar panel systems equipped with tracking devices are more effective and efficient compared to static solar panels.